Exports to the US and imports from China during the US-China tariff war: Evidence from regional trade data in Vietnam - Kazunobu Hayakawa (KDI Journal of Economic Policy, 2024)
This study empirically investigates how the exports of downstream products to the US change the imports of their upstream products from China during the US-China tariff war. To accomplish this, we use province-level trade data in Vietnam, known to be a country that increased its exports to the US market in place of China, i.e., known to enjoy a trade diversion in the US market. The use of regional trade data enables us to capture the input-output linkages more precisely. Specifically, focusing on the trade in general and electrical machinery industries from January of 2019 to December of 2023, we regress imports of upstream products from China on exports of their downstream products to the US, finding that the rise of exports of downstream products to the US significantly increases imports of their upstream products from China. On the other hand, the rise in these products does not significantly increase the imports of upstream products from Japan, Korea, and Taiwan. Furthermore, the input- output linkage between exports to the US and imports from China was found to be greater in provinces with better business environments in terms of entry costs, transparency in public services, and public support to businesses.
Keywords: F15; F53; 330; US-China Trade War; Vietnam; Input-output Linkages